Challenges and Opportunities of Inland Fisheries with an SDG Approach: a Systematic Review - Reyes Bedriñana, Magno Rosendo (2025)
Objective: to analyze the challenges and opportunities of inland fisheries for sustainable development. Theoretical Framework: Inland fishing represents a relevant activity today because it is considered a source of economic income and food for the community that practices it. Method: It was developed under the qualitative approach with a systematic review design; the population and sample has been made up of 17 scientific articles extracted from Scopus, Scielo and Web Of Science, which were identified after using the keywords "Inland fisheries" and "sustainable development". Results and Discussion: After the review and analysis of the content of the selected articles, it was evident that inland fisheries are characterized by presenting a mixed trend and facing significant challenges; therefore, environmental, social, economic and management factors have a greater impact on its development, so its challenges are associated with technical limitations. structural and educational institutions, and provides several relevant opportunities. Research Implications: It was concluded that inland fisheries must be developed in a sustainable way taking into account regulatory regulation, population requirements and community reality, in such a way that it contributes to the achievement of the SDGs and ensures the balanced growth of society. Originality/Value: This research addresses a relevant problem in the global context, since inland fisheries play an essential role in food security, local economy and conservation of environmental resources. In this sense, it stands out for its innovative approach and the ability to study a complex reality from a holistic point of view, which is why its contribution to the field of fishing activity because it provides a series of conceptual and practical resources that contribute to the management of challenges and ensures the use of the opportunities that arise.